Human Capital and Macro-Economic Development : A Review of the Evidence - Rossi, Federico (World Bank, Washington, DC, 2018)
This paper reviews the evidence on the importance of human capital for macro-economic development. Through the lens of a simple aggregate production function, human capital might increase output per capita by directly entering in the production process, incentivising the accumulation of complementary inputs and facilitating the adoption of new technologies. The paper discusses the advantages and limitations of three methodological approaches that have been used to evaluate the importance of these channels: cross-country regressions, development accounting and quantitative models. The key findings in the literature are reviewed, and some of them are replicated using updated data. The bulk of the evidence suggests that human capital is an important determinant of cross-country income gaps, especially when its measurement is broadened to go beyond simple proxies of educational attainment. The paper concludes by highlighting promising avenues for future work.